Topical steroid awareness and abuse: A prospective study among dermatology outpatients - T S Nagesh; A Akhilesh (Wolters Kluwer Medknow Publications, 2016)
Background: Topical steroids are one of the most commonly abused drugs. There are only a few studies available which have highlighted the severity of this problem in India. However, these studies have concentrated mainly on the topical steroid abuse and its side effects over the face. Aims: The aim of this study was to know the awareness among the people about various commonly available topical steroids and their combinations irrespective of usage and to know the extent of misuse of these drugs. Along with this, we also tried to find the source of recommendation of these medicines which will help to sensitize people about this menace. Materials and Methods: This was a prospective, questionnaire-based study done at a tertiary care hospital. A total of 1000 adult patients attending the dermatology outpatient department were administered a questionnaire about awareness and usage of topical steroid and its combinations. Results: A total of 1000 adult patients were included in the study, out of which 809 (80.9%) patients had heard about at least one of the topical steroids or its combinations mentioned in the questionnaire. Six hundred and twelve (61.2%) patients had used these creams. Acne and pigmentation were the most common indications for which topical steroid was used. These medicines were recommended by general practitioners in 302 (49.5%) patients and pharmacists in 71 (11.6%) patients. Totally, 318 (51.9%) patients complained of some form of side effect after using these creams. Aggravation of the symptoms and increased pigmentation were the most common adverse effects. Conclusion: Misuse of topical steroids not just over the face but also as a cream for any skin problem is quite common. Most of the times, it is recommended by general practitioners or pharmacists. It is very important to sensitize these people about the possible complications of these drugs and the extent of problem the society is facing because of irrational and unregulated use of these drugs.